Aneurysmal Bone Cyst of the Rib – A Rare Chest Wall Tumor - Niaz Hussain Soomro; Anum Javed; Sana Wahab; Anum Deedar (Journal of the Dow University of Health Sciences, 2015)
A 28 year old female presented with the complaint of painful chest wall swelling on the left side anteriorolaterally, for the past three years. Her Trucut biopsy was inconclusive. Incisional biopsy proved it to be aneurysmal bone cyst. It was excised and chest wall was reconstructed with propylene mesh and muscle flaps. Her postoperative recovery was smooth.